THE IMPORTANCE OF CALCIUM METABOLISM IN WOMEN DURING MENOPAUSE AND ITS IMPACT ON THE BODY - Masharipova Salimaxon Ortikaliyevna (Web of Journals Publishing, 2025)
This research article provides an in-depth analysis of changes in calcium metabolism in women during menopause and its effects on the body. It discusses the disruption of calcium assimilation caused by the decrease in estrogen levels, leading to bone mass loss and the development of osteoporosis from a scientific perspective. The article extensively explores the biochemical mechanisms of calcium metabolism, the physiological changes occurring during menopause, the process of bone tissue remodeling, and their overall impact on the body. The research findings highlight diseases resulting from calcium deficiency during menopause, their prevention methods, and treatment strategies. The article also provides information on the use of calcium supplements, vitamin D support, and other preventive measures.
Keywords: menopause, calcium metabolism, estrogen, osteoporosis, bone density, vitamin D, calcium assimilation, bone remodeling, postmenopause, parathyroid gormone, calcitonin, mineral metabolism, women’s health, endocrine system, bone diseases.